2019
DOI: 10.1186/s13059-019-1810-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic underestimation of the epigenetic clock and age acceleration in older subjects

Abstract: BackgroundThe Horvath epigenetic clock is widely used. It predicts age quite well from 353 CpG sites in the DNA methylation profile in unknown samples and has been used to calculate “age acceleration” in various tissues and environments.ResultsThe model systematically underestimates age in tissues from older people. This is seen in all examined tissues but most strongly in the cerebellum and is consistently observed in multiple datasets. Age acceleration is thus age-dependent, and this can lead to spurious ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
95
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 99 publications
(121 citation statements)
references
References 51 publications
21
95
0
Order By: Relevance
“…Applying predictors to datasets that differ in terms of these characteristics may lead to biases when estimating DNAm age, and confound phenotypic analyses using these variables (El Khoury et al, 2019). We found that existing DNAm clocks (i.e.…”
Section: Existing Dnam Clock Algorithms Work Sub-optimally In the Hummentioning
confidence: 93%
See 4 more Smart Citations
“…Applying predictors to datasets that differ in terms of these characteristics may lead to biases when estimating DNAm age, and confound phenotypic analyses using these variables (El Khoury et al, 2019). We found that existing DNAm clocks (i.e.…”
Section: Existing Dnam Clock Algorithms Work Sub-optimally In the Hummentioning
confidence: 93%
“…Briefly, to predict DNAm age using the DNAmClockMulti we applied the agep() function in wateRmelon (Pidsley et al, 2013). Although this function does not contain the custom normalisation method applied at the DNAm age calculator website (https://DNAmClock.genetics.ucla.edu/), both methods work similarly in brain and blood studies, providing the data have been pre-processed adequately (El Khoury et al, 2019).To predict age using the DNAmClockPheno (Levine et al, 2018), we also applied the agep() function, inputting a vector of the coefficients and the intercept using the data provided in the supplementary material of Levine et al's manuscript. To predict DNAm age with the DNAmClockblood, we used the authors' published code (available on GitHub https://github.com/qzhang314/DNAm-based-age-predictor) (Zhang et al, 2019).…”
Section: Deriving a Novel Cortical Dnam Age Classifiermentioning
confidence: 99%
See 3 more Smart Citations